Determination of Serum isocitric dehydrogenase in Patients with Hepatobiliary Diseases - Cremer Nicoli, Guillermo (1965)
The remarkable progress made in Enzymology during recent years , have found prompt and useful application in various fields of medical science . Today there are many diseases attributable to disturbances in the activity of specific enzymes or enzyme systems ; on the other hand the effects of many drugs depend on their influence on enzymatic processes ; various enzymes that are today found useful application in modern therapeutics ; finally determining enzyme s also increasing use in the diagnosis and differential diagnosis of various diseases . These and many other reasons make hold Abderhalden ( 1), which are currently on the threshold of a new phase - in the development of medicine, Clinical Enzymology era . Enzymes , organic catalysts , are responsible for most of the chemical reactions of the organism , and are widely distributed in all tissues . Enzymatic determinations do in the digestive juices , urine , blood, cerebrospinal fluid and tissue biopsies , allowing a better understanding of normal and pathological physiology. However, for diagnostic purposes , the determination of enzymes is confined almost exclusively to the blood , and serum actually .